The prevalence of dysfunctional breathing in adults in the community with and without asthma - Thomas, Mike (Prim Care Respir J, 2005)
Functional breathing problems, including symptomatic hyperventilation, may impair quality of life. Symptoms associated with functional breathing disorders have been reported as being common in secondary care settings, and can affect 29% of adults with current asthma in the community. The prevalence of dysfunctional breathing in the general adult population is unknown. The Nijmegen Questionnaire has been reported to have useful sensitivity and specificity for diagnosing dysfunctional breathing. A cross-sectional postal survey of adults without current asthma was undertaken in a single UK general practice. The results were analysed in conjunction with a previously described survey of adults with current asthma from the same population. The questionnaire was posted to a random sample of 300 people aged 16–65 without current asthma, and 69% were returned. 8% (95% confidence intervals 4–12%) had positive screening scores. Positive screening scores were more common in women (14%, 7–20%) than men (2%, 0–5%, p=0.003). Comparison with the previous survey showed that the prevalence of positive screening scores was higher in those with current asthma than those without (29% vs. 8%, p < 0.001). Dysfunctional breathing may affect up to one in 10 people, and is more common in women and in people with asthma.